2010
DOI: 10.1111/j.1365-2958.2010.07334.x
|View full text |Cite
|
Sign up to set email alerts
|

ABI domain‐containing proteins contribute to surface protein display and cell division in Staphylococcus aureus

Abstract: Summary The human pathogen Staphyloccocus aureus requires cell wall anchored surface proteins to cause disease. During cell division, surface proteins with YSIRK signal peptides are secreted into the cross wall, a layer of newly synthesized peptidoglycan between separating daughter cells. The molecular determinants for the trafficking of surface proteins are, however, still unknown. We screened mutants with non-redundant transposon insertions by fluorescence-activated cell sorting for reduced deposition of pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 73 publications
1
48
0
Order By: Relevance
“…Three other genes in the WTA interaction network (lyrA, 965, and SAOUHSC_02256) encode structurally related membrane proteins that resemble type II CAAX prenyl endopeptidases, a family of proteins well known in eukaryotes because key members are involved in the proteolytic processing of prenylated Ras and other lipoproteins (30). There are five genes encoding CAAX protease-like (CPL) homologs in S. aureus, including the three identified in the growth depletion analysis, but only ΔlyrA mutants have been characterized (31,32). These mutants have altered crosswall structures and are deficient in a subset of surface proteins, but as yet there is no evidence that LyrA has a proteolytic function.…”
Section: Linkage Analysis Provided Gene-gene Validation Of Compound-genementioning
confidence: 99%
“…Three other genes in the WTA interaction network (lyrA, 965, and SAOUHSC_02256) encode structurally related membrane proteins that resemble type II CAAX prenyl endopeptidases, a family of proteins well known in eukaryotes because key members are involved in the proteolytic processing of prenylated Ras and other lipoproteins (30). There are five genes encoding CAAX protease-like (CPL) homologs in S. aureus, including the three identified in the growth depletion analysis, but only ΔlyrA mutants have been characterized (31,32). These mutants have altered crosswall structures and are deficient in a subset of surface proteins, but as yet there is no evidence that LyrA has a proteolytic function.…”
Section: Linkage Analysis Provided Gene-gene Validation Of Compound-genementioning
confidence: 99%
“…Bacterial lysates and supernatants were prepared as described previously (27), with modifications. Please refer to the supplemental material for details.…”
Section: Methodsmentioning
confidence: 99%
“…The exact mechanism by which PncO regulates bacteriocin production or mediates immunity is currently unknown. CPBP proteins have also been shown to be involved in the expression of surface proteins containing the YSIRK signal peptide, as in the case of Staphylococcus aureus Spd proteins (73). Recently, Firon and colleagues have shown that in S. agalactiae, a CPBP protein, Abx, forms a signaling complex with the histidine kinase CovS and regulates expression of virulence factors (74).…”
Section: Discussionmentioning
confidence: 99%